2018
DOI: 10.3390/pr6010003
|View full text |Cite
|
Sign up to set email alerts
|

On the Thermal Self-Initiation Reaction of n-Butyl Acrylate in Free-Radical Polymerization

Abstract: This experimental and theoretical study deals with the thermal spontaneous polymerization of n-butyl acrylate (n-BA). The polymerization was carried out in solution (n-heptane as the solvent) at 200 and 220 • C without adding any conventional initiators. It was studied with the five different n-BA/n-heptane volume ratios: 50/50, 70/30, 80/20, 90/10, and 100/0. Extensive experimental data presented here show significant monomer conversion at all temperatures and concentrations confirming the occurrence of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Furthermore, the two singlets at 5.80 and 6.20 ppm recall the pattern of geminal hydrogens of a substituted double bond and were tentatively attributed to radical reactions between the acrylamide terminals formed in each retro-aza-Michael step. Radical dimerizations are, for instance, the basis of spontaneous thermal and photochemical self-polymerization of vinyl monomers [ 57 , 58 , 59 , 60 ]. It may be observed that the degrading samples were purposely maintained for months in natural conditions of temperature and light.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the two singlets at 5.80 and 6.20 ppm recall the pattern of geminal hydrogens of a substituted double bond and were tentatively attributed to radical reactions between the acrylamide terminals formed in each retro-aza-Michael step. Radical dimerizations are, for instance, the basis of spontaneous thermal and photochemical self-polymerization of vinyl monomers [ 57 , 58 , 59 , 60 ]. It may be observed that the degrading samples were purposely maintained for months in natural conditions of temperature and light.…”
Section: Discussionmentioning
confidence: 99%
“…There was no need to use an initiator. AAc has high tendency for thermal self-initiation in bulk [36,37] and H 2 SO 4 has an accelerating effect on its polymerization. [38] Also, any solvent was not used in the preparation of the pregel solution because AAc and TX-100 were homogeneously miscible with each other.…”
Section: Hydrogel Preparation Swelling and Gel Fraction Measurementsmentioning
confidence: 99%
“…The Special Issue also contains two contributions focusing on polymerization processes. One paper investigates the experimental validation of a kinetic model for thermal spontaneous polymerization of n-butyl acrylate) [13], while the other paper presents a MATLAB-based tool for copolymerization reactivity ratio estimation based on error-in-variables models [14]. The sixth paper in this area addresses the problem of materials processing through the development of a classification method for identifying a promising experimental design region from a literature database [15].…”
Section: Materials Processesmentioning
confidence: 99%